ENVIRONMENTAL MODELS OF AGING - Izal, María; Fernández-Ballesteros, Rocío (Anales de Psicología / Annals of Psychology)
Person-environment relations through age have been forgotten into psychological research for many years. The main scope of this paper is the presentation of the principal theoretical models of the person-environment relations in old age in a critic way. Finally, conceptual and methodological alternatives are proposed in order to develop this field.